Reforming Pedagogy in Indonesian Primary Schools: A Five-Year Systematic Review of Differentiated Instruction, Project-Based Learning, and Formative Assessment (2020–2025) - Kristiyuana, Kristiyuana; Wuriningsih, FR.; Idammatussilmi, Idammatussilmi; Agung, Anugrah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study aimed to explore the implementation of Indonesia’s Independent Curriculum in elementary schools, focusing on three pedagogical aspects: differentiated instruction, project-based learning (PBL), and formative assessment. A systematic review of literature published between 2020 and 2025 was conducted to identify emerging trends and challenges in applying these strategies. The findings indicate that the Independent Curriculum’s student-centered approach has led to more personalized and active learning experiences. Differentiated instruction is promoted to meet diverse student needs, and early evidence suggests it can improve student engagement and learning outcomes. PBL, exemplified by interdisciplinary projects to strengthen the Pancasila Student Profile, has fostered critical thinking and collaboration. Likewise, formative assessment practices are increasingly adopted, shifting the focus from high-stakes exams to continuous feedback on student learning. However, significant challenges were identified. Many teachers face difficulties in designing differentiated lessons and PBL activities due to varying student abilities, limited resources, and insufficient training. Adapting to a holistic, formative assessment approach has also proven challenging for educators accustomed to traditional testing. Based on these findings, the study provides practical recommendations for stakeholders, including enhanced teacher professional development, improved infrastructure support, and collaborative strategies to overcome implementation barriers. This synthesis offers insights into the progress of Independent Curriculum in primary education and underscores the need for ongoing support to realize its student-centered vision fully.